Peran Pendidik Dalam Mendorong Keaktifan Berbahasa di Kelas - Amalia, Kartika; Aulia, Regina Putri; Putra, Audryan Avia (PT. Alahyan Publisher Sukabumi, 2023)
Educators have a crucial role in encouraging language activity in the classroom. This study explores the role of educators in stimulating students' active participation to communicate orally and in writing. Using qualitative methods by conducting observations, interviews, and literature analysis, this study analyzes the strategies used by educators to increase language activity in the classroom. The results highlight that effective educators play a dual role as facilitators and motivators. Educators create supportive environments, provide constructive feedback, and utilize a variety of active learning techniques to encourage students to speak and write with confidence. The use of role plays, group discussions, collaborative projects, and reflective writing assignments are some of the effective strategies used to generate student interest and engagement in the classroom.